Difficulties in the removal of whistle foreign body in the left bronchus - Handayani, Ni Komang Tri Utami; Sucipta, I Wayan; Putra, I Dewa Gede Arta Eka; Asthuta, Agus Rudi; Suanda, I Ketut; Dewantara, I Putu Santhi (Oto Rhino Laryngologica Indonesiana, 2025)
Background: Tracheobronchial foreign bodies are one of the most common critical conditions in otorhinolaryngology. The mortality rate due to foreign body aspiration in children under 5 years old is quite high. The increased incidence of foreign body aspiration was triggered by the tendency of children to put everything in their mouths when crying, screaming, running, and playing. Purpose: To report difficulties in the management of a whistle foreign body in the left bronchus. Case report: A 9 years old boy, was brought to Prof. Ngoerah Hospital on December 19th, 2023, with a complaint of coughing for 2 days, because he accidentally choked on a whistle while playing. However, the results of thoracic X-ray and CTscan did not show a clear foreign body in the form of a whistle. Method: Literature search was conducted using keywords ”whistle foreign body in left bronchus” OR ”whistle foreign body” OR ”foreign body in left bronchus” AND ”bronchoscopy management” in Medline and PubMed from 2019– 2024. Result: A total of 21 literatures was found, and 12 could be used as references. Conclusion: The management of foreign body in the bronchus is challenging in diagnostic and bronchoscopy procedures.